Accessibility analysis for transportation projects and plans. (October 2018) - Merlin, Louis A.; Levine, Jonathan; Grengs, Joe
Highlights: A method for analyzing the accessibility impact of specific, proposed transportation projects is demonstrated. Two suites of transportation projects are compared for their 10-year accessibility impacts in San Antonio, Texas. Land-use forecasts are incorporated to account for how these transportation projects alter future land-use patterns. Accessibility impacts are compared and contrasted with mobility impacts, with strongly differing outcomes.